Study on Use of Lactoferrin for the Biopreservation of Paneer - CSS Shashikumar; DB Puranik (Tropical Agricultural Research, 2012)
Paneer is an Indian traditional milk product which occupies an important place as a base product for the production of various culinary preparations. The shelflife of paneer is a major constraint in its utilization. Lactoferrin, a member of transferrin family of proteins, is one of the most important milk proteins naturally found in the milk of mammals and is an iron-binding glycoprotein which has antimicrobial properties. Studies were conducted on incorporation of lactoferrin at different levels (10, 15 & 20 ppm) in paneer. It was observed that, as the level of lactoferrin in the product increased, there was a significant decrease in the bacterial growth when compared to the control; thereby increasing the shelflife of paneer. Lactoferrin-treated paneer, up to 20 ppm showed an increase in shelf life up to 7 days at room temperature (30°C) and 15 days at refrigerated temperature (4°C) compared with the control with a shelf life of 2 days at 30°C and 7 days at 4°C, respectively. Similarly, as the level of lactoferrin increases, paneer had significantly higher hardness, cohesiveness, springiness and chewiness. The sensory evaluation of the paneer samples treated with 20 ppm lactoferrin was acceptable up to 7 days at ambient temperature and up to 15 days at refrigerated temperature. Tropical Agricultural Research Vol. 23 (1): 70-76 (2011) DOI: http://dx.doi.org/10.4038/tar.v23i1.4633